Diagnosis of hemoperitoneum by paracentesis "a minimal": False paracentesis on white - Perdomo, Roberto (Cirugía del Uruguay, 1976)
The authors describe and illustrate a simple and practica! procedure to recognize the hemoperitoneum in only one drop of fluid obtained by paracenthesis and deposited on a glass plate. They remark that this procedure it is possible to · bring forth even minimal hematíe shedding, and to reduce, drastically, the number of false negative findings in paracenthesis. Punctures which had been considered negative are now included in the positive finding group. With the use of this method it is possible avoid more complex methods which are based on the necessity to objectivize a larger volume of fluid in order to make the diagnosis of hemoperitoneum certain, and which use catheters with or without peritoneal lavage in order to increase the efficiency of the simple paracenthesis.